A Retrospective Look at Recent COVID-19 Articles Published in Cell Transplantation: Research Leading to Further Understanding. (22nd October 2021) - Sanberg, Paul; Morrison, Donna C; Kovacs, Ryan A; Bjugstad, Kimberly
During the past 18 months as the world dealt with the COVID-19 pandemic, articles published in Cell Transplantation ( CT ) voiced unique perspectives on the disease which have since been supported by additional research. Intrigued by the variability in COVID-19 severity, CT authors explored the influence of variants in angiotensin-converting enzyme 2 (ACE2) and the transmembrane serine protease 2 (TMPRSS2) genes, as well as the role of androgen receptors on disease development. Mesenchymal stem cells (MSC) were offered up as a potential COVID-19 therapy because of their immune modulating characteristics and successful use in other acute respiratory diseases. Two CT author groups gave proof of principle when hospitalized COVID-19 patients were infused with MSC after no other interventions seemed to work. MSC treatment reduced disease severity and shortened hospitalization stays. Lastly, CT authors speculated why we are still in the midst of a pandemic and the consequences of disillusioned comfort as we face new emerging variants that may undermine all we have accomplished thus far.